2020
DOI: 10.1186/s12879-020-05658-4
|View full text |Cite
|
Sign up to set email alerts
|

Pilot implementation of a home-care programme with chlamydia, gonorrhoea, hepatitis B, and syphilis self-sampling in HIV-positive men who have sex with men

Abstract: Background Not all men who have sex with men (MSM) at risk for sexually transmitted infections (STIs) and human immunodeficiency virus (HIV) infection currently receive sexual healthcare. To increase the coverage of high-quality HIV/STI care for MSM, we developed a home-care programme, as extended STI clinic care. This programme included home sampling for testing, combined with treatment and sexual health counselling. Here, we pilot implemented the programme in a hospital setting (HIV-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Thirty-three studies identified home-based self-testing or self-sampling as the preferred method of testing [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 , 26 , 29 , 31 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] ( Table 2 ). Three randomised controlled trials (RCT) found that HIVST increased testing frequency, and therefore was preferred by MSM compared to usual testing [ 17 , 21 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-three studies identified home-based self-testing or self-sampling as the preferred method of testing [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 , 26 , 29 , 31 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] ( Table 2 ). Three randomised controlled trials (RCT) found that HIVST increased testing frequency, and therefore was preferred by MSM compared to usual testing [ 17 , 21 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Confidentiality or privacy was identified to be a common reason for preferring self-testing amongst MSM [ 14 , 25 , 27 , 34 , 49 , 51 , 52 , 60 ]. One study, conducted in the Netherlands, used semi-structured interviews to explore key factors which allowed for the successful implementation of social network testing with HIV self-tests [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequent HIV/STI testing plays an important role in the control of HIV/STI transmission, because it enables timely diagnoses and treatment and shortens the duration of infection [44]. Besides optimizing outcomes after diagnosis for individuals benefit, early treatment shortens the duration of an infected individual to spread the infection, benefitting the public health by using treatment as a prevention for HIV spread [45][46][47]. Studies have proposed that MSM who receive antiretroviral therapy (ART) and have achieved and maintained an undetectable viral load cannot sexually transmit the virus to others, controlling transmission [45,46,48].…”
Section: Decrease Duration Of Infectiousness: Testing and Treatmentmentioning
confidence: 99%
“…The STI clinic will send tailored SMS reminders. Reminders (text messages) will be used to promote testing behavior, as reminders have proven to increase participation [45,46]. The text messages will also…”
mentioning
confidence: 99%